Parallel cyclic codes - Semerenko, V. P. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The compound and integrated parallel cyclic codes for multichannel transmission systems with transferring of the different code words in different channels are presented. Methods of encoding and decoding of these codes based on multichannel linear finite-state machines are developed. The analysis of correcting capability of the parallel cyclic codes and methods of its increasing is carried out in the paper.